A New Arena of Herbal Nanotechnology - Sharma, Urvashi (Asian Journal of Pharmaceutics (AJP), 2024)
Herbal drugs have been used since ancient times due to their renowned therapeutic efficacy and safety parameters. Today, people are shifting more frequently from synthetic substances to herbal compounds for drug-related needs. The major problems with phytocompounds are their limited aqueous solubility, degradation in acidic pH, etc. The answer to this came with the recent developments in nanotechnology, which allow the creation of nanoparticles with enormous potential as drug delivery systems due to their reduced size up to the nanoscale. Drugs undergoing nanoscale transformations have distinctive properties, such as enhanced drug efficacy, extended circulation, improved drug localization, and increased solubility. Herein, a new era of nano-phytomedicine has been discussed that ensures the delivery of bioactive compounds and diagnostics to a target site by exploiting various carriers. The review also summarizes the processes for the synthesis of nanoparticles and their characterization parameters, with the pivotal role of nanotechnology in recent applications exploiting novel phytoconstituents.